Electrochemical, spectroelectrochemical and electrocatalytic properties of newly synthesized phthalocyanine compounds with 1,1 '-thiobis(2-naphthol) groups - ÖZKAYA, ALİ RIZA (ELSEVIER, 2019)
In this work, the synthesis and characterization of new phthalocyanine compounds containing 1,1'-thiobis(2-napthol) units have been reported. The metal-free phthalocyanine, H2Pc 3 was synthesized by the cyclotetramerization of dinitrile derivative 2 in dry n-pentanol by a classical method. Metal phthalocyanines complexes, ZnPc 4 and CoPc 5 were prepared by the reaction of 2 with the corresponding anhydrous metal salts in n-pentanol and DBU. The structures of the original compounds were identified by using elemental analysis, H-1 NMR, C-13 NMR, IR, mass and UV-vis spectroscopic data. Electrochemical redox characteristics of the compounds were determined by electroanalytical techniques such as cyclic voltammetry, square wave voltammetry, and chronocoulometry. Extra support for the precise nomination of the electron transfer processes were also maintained with in situ spectroelectrochemical measurements. The compounds usually showed one-electron metal- and/or ligand-based reversible or quasi-reversible reduction and oxidation processes. The processes were found to be accompanied by distinct colour changes, indicating the possibility of the use of the compounds as electrochromic material. Electrocatalytic oxygen reducing performances of the compounds were also tested by dynamic voltammetry in a medium similar to fuel-cell working conditions. The CoPc compound showed high performance for electrocatalytic reduction of dioxygen to water through a process involving the transfer of totally 4 electrons per molecule in two different ways. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Cyclotetramerization; Phthalocyanine; Electrochemistry; Spectroelectrochemistry; Electrocatalysis; GAS-SENSING PROPERTIES; SUBSTITUTED METAL-FREE; OXYGEN REDUCTION; INCLUSION COMPLEXES; CO(II); ZN(II); TETRA; METALLOPHTHALOCYANINES; AGGREGATION; BEHAVIOR